Draft Genome Sequence of Plant Growth-Promoting Rhizobacterium Burkholderia sp. Strain USMB20, Isolated from Nodules of Mucuna bracteata - Aziz, Nurohaida Ab (Microbiol Resour Announc, 2021)
Burkholderia sp. strain USMB20 is a plant growth-promoting rhizobacterium that was isolated from nodules of the leguminous cover crop Mucuna bracteata. The draft genome sequence of Burkholderia sp. strain USMB20 has an assembly size of 7.7 Mbp in 26 contigs with a GC content of 66.88%.